Analysis of the influence of fatigue on passenger transport drivers’ performance capacity - Zaranka, Jurijus; Pečeliūnas, Robertas; Matijošius, Jonas (Transport, 2012)
The article deals with the influence of professional drivers’ fatigue on the occurrence of traffic events. The study of various scientific works on the causes of traffic events related to human psychophysiological qualities has revealed that all of these works highlight the complex work process of a driver as an operator of a certain mechanism. It is governed by the regulatory documents reviewed in this article. Driver’s fatigue is a quite frequent accident-causing human factor. Building upon the results of the study on human idiosyncrasies, the authors suggest a methodology for professional selection of drivers. This methodology is based on practical data, i.e. on a comprehensive analysis of performance peculiarities of professional drivers employed at Joint-Stock Company ‘Vilnius Public Transport’ (in Lithuanian – UAB ‘Vilniaus viešasis transportas’). Application of the suggested methodology enables to reduce the number of road accidents caused by city passenger transport drivers by up to 40÷50%. The article proposes a methodology for compilation of professional selection criteria for passenger transport drivers, also applicable to drivers working in other transportation areas, as well as to employees of field investigation services and other persons who constantly face nervous and emotional stress and experience a lack of information and time. First Published Online: 21 Dec 2012